Modelagem de multiplicação de Staphylococcus aureus nas fases planctônica e séssil em diferentes superfícies de contato - Rumão, Jaqueline da Silva (2021)
Food quality and safety are important factors that need to be ensured during all stages of food production. The great challenge in the food sector is the control of microbial multiplication, as microorganisms increasingly seek survival strategies from the different antimicrobial agents present in the environment. Staphylococcus aureus is one of the microorganisms most involved in cases of food contamination, in addition, it can adhere to equipment and industrial surfaces and form biofilms. Due to this concern, new strategies are taken to understand the dynamics of microbial growth, and predictive microbiology is gaining more and more space in the field of food microbiology. Therefore, the aim of this work was to apply predictive microbiology in the growth of S. aureus in planktonic and sessile phases on different food contact surfaces. Therefore, in this study, the strain of S. aureus ATCC 25923 was used, and the surfaces of glass, stainless steel, polypropylene, high-density polyethylene, and low-density polyethylene were used as specimens. To verify the growth curve of S. aureus in the planktonic and sessile phases, a temperature of 15º C was used at times 0 h, 24 h, 48 h, 72 h, 96 h, 120 h, 144 h and 168 h. Then, there was the quantification of microorganisms in planktonic and sessile forms. According to the results, there was growth of S. aureus in the planktonic phase as well as the formation of biofilm on all contact surfaces evaluated, therefore, the curves performed in ComBase by means of DMFit show that there was a good fit of the model with respect to the prediction of free cells and cells adhered to substrates. The surfaces of polypropylene, high density polyethylene and low-density polyethylene provided an immediate adhesion of the microorganism to the substrates at time 0, while on the glass and stainless-steel surfaces this adhesion only started after 24 hours of adaptation. Scanning electron microscopy showed the structural architectures of the mature biofilm and confirmed bacterial fixation on all surfaces with biofilm development evident on all spheres evaluated at a time of 168 hours. Data were subjected to analysis of variance and means were compared by Tukey test at 5% significance, obtaining a significant difference (P<0.05) between all surfaces studied. Therefore, it is concluded that the predictions performed in the ComBase Predictor by means of DMFit were satisfactory for both planktonic and sessile cells, and from all surfaces that showed fast adhesion of S. aureus were the polymers. Therefore, the use of predictive microbiology is a strategy to control microbial multiplication and biofilm formation on surfaces in the food industry.